Empowering Leadership berpengaruh terhadap Kinerja Pegawai Melalui Kecerdasan Emosional - Elsa Salavina; Sih Darmi Astuti (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of empowering leadership on employee performance through self-efficacy, bureaucratic reform, and emotional intelligence. In this study, 49 employees in Social Service were used as samples. The analytical method uses multiple regression analysis using SPSS version 24. The results show that empowering leadership has the strongest effect on the formation of emotional intelligence which has an impact on employee performance. Besides that, empowering leadership will also increase bureaucratic reform which has an impact on employee performance and finally that empowering leadership influences employee performance through self-efficacy.